1998
DOI: 10.1002/(sici)1097-0010(199805)77:1<45::aid-jsfa1>3.3.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Determination of anthocyanins, flavonoids and phenolic acids in potatoes. I: Coloured cultivars of Solanum tuberosum L

Abstract: :The major anthocyanins, Ñavonoids and phenolic acids in the tubers (skin and Ñesh), Ñowers and leaves of 26 cultivars of Solanum tuberosum L with coloured skins and/or Ñesh have been identiÐed and quantiÐed using analytical HPLC. Red tubers contained mostly pelagonidin-3-(p-coumaroyl-rutinoside)-5-glucoside (200È2000 lg g~1 FW) plus lesser amounts of peonidin-3-(pcoumaroyl-rutinoside)-5-glucoside (20È400 lg g~1 FW). Light to medium purple tubers contained petunidin-3-(p-coumaroyl-rutinoside)-5-glucoside (1000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
146
2
11

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(183 citation statements)
references
References 15 publications
24
146
2
11
Order By: Relevance
“…In the first method, an attempt was made to measure the quantity of original anthocyanins without the sample preparation process involving hydrolysis. Considering that red or pink potatoes (peel and tuber) contain pelargonidin-3-(pcoumaryolyrutinoside)-5-glucoside as the main anthocyanin component, while the purple or blue potatoes contain petunidin-3-(pcoumaroylrutinoside)-5-glucoside as the predominant anthocyanin (Lewis, Walker, Lancaster, & Sutton, 1998), we used pelargonidin-3-glucoside and petunidin-3-glucoside as standards to quantify the total anthocyanins in these 20 potato clones (Table 1). Among the red or pink potatoes, clone 15 contained the highest amount of anthocyanins, with a total of 25.79 mg/g dry weight in peel, 14.42 mg/g in tuber, and 10.82 mg/g in granule (measured as pelargonidin-3-glucoside equivalents).…”
Section: Anthocyanins Contentmentioning
confidence: 99%
“…In the first method, an attempt was made to measure the quantity of original anthocyanins without the sample preparation process involving hydrolysis. Considering that red or pink potatoes (peel and tuber) contain pelargonidin-3-(pcoumaryolyrutinoside)-5-glucoside as the main anthocyanin component, while the purple or blue potatoes contain petunidin-3-(pcoumaroylrutinoside)-5-glucoside as the predominant anthocyanin (Lewis, Walker, Lancaster, & Sutton, 1998), we used pelargonidin-3-glucoside and petunidin-3-glucoside as standards to quantify the total anthocyanins in these 20 potato clones (Table 1). Among the red or pink potatoes, clone 15 contained the highest amount of anthocyanins, with a total of 25.79 mg/g dry weight in peel, 14.42 mg/g in tuber, and 10.82 mg/g in granule (measured as pelargonidin-3-glucoside equivalents).…”
Section: Anthocyanins Contentmentioning
confidence: 99%
“…Published data on the degree of variation of antioxidant activity or phenolic content of these native potatoes is not known. As indicated by various studies, colored potatoes provide a natural source of phytochemicals such as carotenoids, phenolic compounds, flavonoids, and anthocyanins (Lewis et al, 1998a;1998b;Reyes and Cisneros-Zevallos, 2003;Reyes et al, 2004) that help reduce the risk of chronic diseases, including cancer, agerelated neuronal degeneration, or cardiovascular diseases (Ames et al, 1993;Hercberg et al, 1998;Velioglu et al, 1998;Tamimi et al, 2002).…”
Section: Researchmentioning
confidence: 99%
“…These include polyphenol, monohydric phenol, coumarin, flavonoid, tannin, and lignin (Lisinska and Leszczynski, 1989). Phenolic compounds such as chlorogenic, ferulic, caffeic, protocatechuic, and p-coumaric acids have been identified in red-or purple-fleshed potatoes (Lewis et al, 1998a). There are also small amounts o flavonoids such as rutin, quercetin, myricetin, naringenin, and kaempferol (Lewis et al, 1998b;Rodriguez-Saona et al, 1998;Reyes et al, 2005).…”
Section: Researchmentioning
confidence: 99%
“…Agria with the lowest TP content was significantly exceeded by Impala (by 51.8%), Magda (by 43.4%) and Marabel (by 40.3%) varieties. Lewis et al (1998) in agreement with our results found that purple-or red-fleshed cultivars had the flavonoid concentration twice higher than white-fleshed cultivars and had three to four times higher the concentration of phenolic acids. Reyes et al (2005) estimated the anthocyanin and total phenolic concentrations of different purple and red flesh potato genotypes in the range from 110 to 1740 mg cyanidin-3-glucoside per kg fresh weight and from 760 to 1810 mg chlorogenic acid per kg fresh weight, respectively.…”
Section: Effect Of Varietymentioning
confidence: 99%